Using system dynamics mapping to explore synergy in an equity-focused obesity prevention framework - Headen, Irene E.; Eaton, Tiffany M.; Kumanyika, Shiriki K. (Frontiers in Public Health, 2025)
IntroductionAddressing health inequities across chronic diseases is a critical public health objective, and policy, systems, and environmental (PSE) change approaches are integral to achieving this goal. However, assumptions about mechanisms of effect or population salience of PSE approaches do not necessarily generalize to inequitable social and economic contexts, partially due to limited ability to operationalize the dynamic complexity of such contexts. Systems thinking applications have the potential to characterize this complexity and improve understanding of where and how to intervene.MethodsThe Getting to Equity in Obesity Prevention Framework (GTE) posits a theory of change involving PSE-related considerations for achieving equity grouped into four categories with a general systems feedback structure. We used systems mapping with a case study to explore the anticipated synergy across categories of the GTE. Data were extracted from a narrative account of childhood obesity prevention initiatives in a predominantly African American and Hispanic, urban public-school district: the Philadelphia Childhood Obesity Declines Project. Project documentation described PSE strategies and contextual influences thought to have contributed to concurrently observed declines in child obesity prevalence and disparities in this population.ResultsOur final dynamic framework, which was anchored by Philadelphia's Universal Feeding Pilot for school meals, identified synergies among intervention strategies. The systems map revealed how planned and unplanned processes accumulated to align with the observed disparities reductions in the participating school district, consistent with the GTE theory of change. Community context dynamics, which evolved over time, were prominent features of the map.DiscussionThis case study enhances the utility of the GTE framework when paired with systems mapping enabled by detailed documentation of PSE initiatives and relevant contextual influences. This suggests that prospective mapping of considerations prompted by the GTE could improve anticipation of unplanned pathways, intervention design, and implementation and supports a need for greater priority for using systems mapping or other systems science tools and methodologies in obesity-prevention research and practice.